The importance of personality toward employee’s performance at Saj Holdings Sdn Bhd Kota Tinggi / Nurulnadia Haron - Haron, Nurulnadia (2014)
The present study investigate the important of personality (Conscientiousness, agreeableness, neuroticism, openness and extraversion), as well as the important of that personality have narrow with employees' performance at SAJ Holdings Sdn Bhd Kola Tinggi. In every part of personalities have their own d:1aracteristics. It was proved by mane researcher that done for their study regarding this topic of personality. The personality also interrelated to the employee’s performance because all of the characteristics were played importance roles while employees in doing work. For this research, the research design that being used in this study was correlation because the researcher want to study the relationship between. personalities towards employees' performance. The respondents that included in this study were 100 employees and the researcher only takes 80 employees for sample size. All of the data were collected from 80 employees in the organization and the data was collected and keyed in into the software Social Science Software (SPSS) 20 version. In addition, the sample technique that being used in this study was simple random sampling where the sampling procedure allowing for the equal and independent chance of subjects being selected as part of the sample. All of the questionnaires that are distribute to the respondents consists of three part which Section A (Demographic Profile), Section B (Types of Personality) and Section C (Employees' Performance). The methods of data analysis for finding have been used for two types which are descriptive statistics and also correlation. The descriptive statistic used to find some general observation about demographic of data such as gender, age, status, education level and work experiences. The correlation is to define the relationship between two variables which are personality (independent variables) and employees' performance (dependent variables). These findings were narrow to the real-world outcomes. Majority, the personality that belongs to the employees was Conscientiousness personality and it was positive affects rather than other personality and the personality that affect to the Quality and Efficiency were Extraversion and Openness personality. All of the personalities also relate to the maximum and typical performance and the level of personality for Openness was typical performance and Extraversion were both of maximum and typical performance.